The Assessment of Plastic Materials for Monitoring the Moisture, Colour, Pungency and Rancidity of 'Chili Boh' - Bakar, Jamilah; Ariff, Arbakariya (1985)
'Chili Boh', which is a slurry of Capsicum annum was prepared in the laboratory and then packaged in heat sealed pouches of polypropylene (PP), low density polyethylene (LDPE), a laminate of polypropylene, cellophane and polyethylene (PPICPPILDPE) and a laminate of oriented polypropylene- polyethylene (OPPIPE). The package samples were stored at ambient temperature and analysed periodically to assess any changes in its moisture, colour, pungency and flavour. Colour was found to be the limiting factor in the shelf-life of the product. The pungency and the flavour (related to degree of rancidity) of the samples were relatively stable up to six weeks. Slight loss of moisture was observed upon storage. PPICPPILDPE and OPPIPE proved to be equally acceptable in maintaining the studied qualities of 'Chili Boh' for up to four weeks. However, OPPIPE is recommended for commercial use due to its low unit cost.